MiR-557 works as a tumor suppressor in human lung cancers by negatively regulating LEF1 expression - Jiayong Qiu; Yingying Hao; Shenshen Huang; Yaqing Ma; Xiaofang Li; Danyang Li; Yimin Mao (Tumor Biology, 2017)
MicroRNAs play an important role in regulating post-transcriptional gene expression in the progression of various human cancers. In this study, we investigated the role of microRNA-557 in human lung cancer cells. The molecular mechanism of microRNA-557 was also clarified in the proliferation and invasion of human lung cancer cells. Our results showed microRNA-557 levels were obviously decreased in clinical lung cancer specimens and lung cancer cell lines. Cell viability of A549 and NCI-H460 cells transfected with microRNA-557 mimics was significantly decreased than those transfected with negative control mimics. MicroRNA-557 promoted cell death of A549 and NCI-H460 but did not affect the cell apoptosis of lung cancer cells. Overexpression of microRNA-557 inhibited cell invasion of A549 and NCI-H460 cells. TargetScan analysis showed that microRNA-557 might target 3′ untranslated region of lymphocyte enhancement factor 1, and the western blotting results showed that transfection of microRNA-557 mimics significantly decreased the levels of lymphocyte enhancement factor 1 in A549 and H460 cells. MicroRNA-557 might work as a tumor suppressor by negatively regulating the expression of lymphocyte enhancement factor 1 in lung cancer cells.